Influence of prior cyclic plasticity on creep deformation using crystal plasticity modelling. (15th May 2018) - Erinosho, T.O.; Venkata, K. Abburi; Mostafavi, M.; Knowles, D.M.; Truman, C.E.
Abstract: This paper proposes a simple, yet effective, modified crystal plasticity framework which is capable of modelling plasticity and creep deformation. In particular, the proposed model is sufficiently versatile to capture the effects of complex load histories on polycrystals, representative of those experienced by real materials in industrial plant. Specifically, the methodology was motivated by the need in the power generation industry to determine whether cyclic pre-straining influences the subsequent creep behaviour of type 316H austenitic stainless steel as compared to non-cyclically pre-strained material. Cyclic pre-straining occurs widely in plant and it is of paramount importance to accurately account for its impact on the subsequent deformation and integrity of relevant components. The framework proposed in this paper considers the effects of dislocation glide and climb in a relatively simple manner. It is calibrated using experimental tests on 316H stainless steel subjected solely to monotonic plasticity and forward creep. Predictions are then obtained for the creep response of the same material after it had been subjected to cycles of pre-strain. The predictions are compared to experimental results and good agreement was observed. The results show slower creep strain accumulation following prior cyclic loading attributed to hardening structures developed in the material during the cyclic pre-strain. The model also highlights the importance of accounting for directionality of hardening under reverse loading. This is hypothesized to affect the development of an internal stress state at an intragranular level which is likely to affect subsequent creep accumulation.